Development of BALIGH Model (Basic, Awareness, Loyalty, Insight, Growth, Help) in Islamic Religious Education to Prepare Students for Aqil Baligh in Pseudo-Maturity Era - Surahman, Cucu; Faqihuddin, Achmad; Muflih, Abdillah (Program Studi Pendidikan Agama Islam, 2025)
This study develops and tests the BALIGH (Basic, Awareness, Loyalty, Insight, Growth, Help) instructional model in Islamic Religious Education to prepare students for aqil baligh amid the challenges of pseudo-maturity. Using an exploratory sequential mixed-methods design, qualitative interviews, document analysis, and classroom observations, this study informed the six-stage syntax; a one-group pretest-posttest trial (N = 60) then examined its effectiveness with a six-dimension aqil baligh readiness scale. Paired t-tests, effect sizes, reliability analysis, and N-gain showed substantial improvement from 33.82 to 61.85 (Δ = 28.03; p < .001; N-gain = 0.695), with no low-gain students. The findings demonstrated that BALIGH effectively integrates conceptual-fiqh strengthening, character formation, help-seeking, and school-family support. The model has contributed a theory-grounded, practically applicable toolkit for puberty-focused IRE, and offers a validated structure for monitoring students’ aqil baligh readiness.